Teachers as actors in an educational design research: What is behind the generalized formula? - Sterner, Helén Elisabeth, Kristina (LUMAT: International Journal on Math, Science and Technology Education, 2019)
Educational design research provides opportunities for both the theoretical understanding and practical explanations of teaching. In educational design research, mathematics teachers’ learning is essential. However, research shows that little consideration is given to teachers and the participation of teachers throughout the entire design process as well as in continued learning. With this in mind, an educational teacher-focused design research was used to explore the challenges teachers face and the opportunities teachers are given when they participate as actors in all the phases of educational design research - designing, teaching, and refining theoretical concepts within the teaching. In this study, the mathematics focus of the design research was generalizations in patterns with Design Principles as the theoretical frame. The results show that the participation of teachers in all the phases of a design process is central for the teachers’ learning. Moreover, challenges that the teachers encounter in the classroom provide opportunities and consequences for the continued design process and lead to changes in the teachers’ understanding of generalizations. The results also indicate that functional thinking and linear equations contributed to both the teachers’ and students’ learning about generalizations in patterns.